Strategi Pembelajaran Inovatif untuk Meningkatkan Kompetensi Siswa - Herliza Syafira Amelia; Dwi Nurul Fitrah Fisshobah; Adelia Eka Dayendria; Bima Wahyuda (Kampus Akademik Publiser, 2025)
Improving student competence is the main focus in the world of education to face the challenges of the 21st century. This article aims to examine innovative learning strategies that can be applied to improve student competence, both in terms of cognitive, affective, and psychomotor. The method used is a literature study by analyzing various innovative learning approaches, such as project-based learning, flipped classroom, and technology integration in the learning process. The results of the study show that these strategies are able to increase learning motivation, student involvement, and critical, creative, and collaborative thinking skills. In addition, the implementation of this strategy also shows the important role of teachers in designing adaptive learning that is relevant to student needs. Thus, innovative learning strategies are a potential solution in creating a competent, adaptive generation that is ready to face global challenges.